Acoustic emission monitoring on damage evolution of surrounding rock during headrace tunnel excavation by TBM. Issue 10 (3rd October 2019) - Hu, Mingming; Zhou, Hui; Zhang, Yonghui; Zhang, Chuanqing; Gao, Yang; Hu, Dawei; Lu, Jingjing
Abstract: The acoustic emission (AE) characteristics of the damage evolution of surrounding rock during tunnel-boring machine (TBM) excavation were studied using AE monitoring and ultrasonic testing. The results indicated that the distribution of the AE signals in the surrounding rock were obtained by the reasonable arrangement of the positions of the probes and the multi-parameter filtering method during TBM excavation. For engineering I, rock damage at different degrees along the direction of the TBM advancement was observed within 5 m ahead of the tunnel face during TBM excavation, while the most severe rock damage appeared 1 m ahead of the tunnel face. The difference in the AE events and energy rates helped distinguish the embedding depths of the loose zone, EDZ and disturbance zone, which were 1, 1–3 and 3–8 m from the tunnel wall, respectively. For engineering II, different degrees of rock damage along the axial tunnel direction were observed within 6 m ahead of the tunnel face, with the most severe rock damage occurring 1 m ahead of the tunnel face. The results can provide significant reference values for the safe and efficient application of TBM excavation in engineering processes.